2021
DOI: 10.3389/fphar.2021.599552
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Complete Remission in Two Patients with Acute Lymphoblastic Leukemia and Severe Fungal Infection Following Short-Term, Dose-Reduced Chemotherapy

Abstract: Spontaneous remission in acute lymphoblastic leukemia (ALL) is a rare phenomenon, which typically involves a pattern of feverish or septic disease followed by quick but mostly transient remission. We report on two male patients (46-year-old (pt. 1) and 19-year-old (pt. 2)) with CD20 positive, BCR-ABL negative common B-ALL. Patient 1 had received dexamethasone and cyclophosphamide (1.2 g) as a prephase therapy, followed by rituximab and a cumulative dose of 200 mg daunorubicin combined with 2 mg vincristine as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This cytotoxic reaction involving γδT cells, which may cause a reduction of leukemic clones and, consequently, eradicate MRD and prevent future relapse, can be triggered by acute infection. This, in turn, might explain why these temporary SR were described in patients presenting with fever [19,20]. Although this patient had two isolated febrile peaks, they were selflimited and associated with IgEV and platelets pool infusions.…”
Section: Discussionmentioning
confidence: 81%
“…This cytotoxic reaction involving γδT cells, which may cause a reduction of leukemic clones and, consequently, eradicate MRD and prevent future relapse, can be triggered by acute infection. This, in turn, might explain why these temporary SR were described in patients presenting with fever [19,20]. Although this patient had two isolated febrile peaks, they were selflimited and associated with IgEV and platelets pool infusions.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, anakoinosis was proposed as a successful way of modulating cancer tissue homeostasis by re-establishing a new equilibrium via "tissue editing" [50]. Pro-anakoinotic drugs act as tissue master modulators, thereby preventing tissue defenses, providing a concerted regulative activity profile of a treatment schedule's single components, and may facilitate long-term tumor control or even continuous complete remission [51][52][53][54]. Importantly, this approach showed that classic pro-apoptotic drugs are un-necessary to induce long-term tumor control or continuous complete remission [55]: anakoinosis would thus bypass the intrinsic limitation of the current pro-apoptotic therapies by aiming at bio-modulation instead of cytotoxicity, possibly avoiding CRAC as suggested by in silico modeling [56].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of spontaneous remissions of ALL have shown periods of temporary remission varying in duration from 14 days to 8 years. 16,17 It should be noted that the longest periods of remission are generally with patients who had SR but also received therapy.…”
Section: Discussionmentioning
confidence: 99%